If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42j + 18 + -19 = -28 Reorder the terms: 18 + -19 + 42j = -28 Combine like terms: 18 + -19 = -1 -1 + 42j = -28 Solving -1 + 42j = -28 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 42j = -28 + 1 Combine like terms: -1 + 1 = 0 0 + 42j = -28 + 1 42j = -28 + 1 Combine like terms: -28 + 1 = -27 42j = -27 Divide each side by '42'. j = -0.6428571429 Simplifying j = -0.6428571429
| 5y+8=2y+2 | | 5x=-2 | | 4(x+2)=4x-10 | | 3p-1=3x-9 | | 3x^2+12x= | | -4(1+5X)-7(-5+8X)=31 | | 3(x-5)-14=2(x-7)+2 | | 2(s-3)=15 | | x-3+2=0 | | -5(m+10)=100 | | 4(x+7)=36 | | 30=-2(1+2N)+8(N+8) | | -2x-1=7+2x | | 4(3x+15)=0 | | -3s+(-4)=25 | | -7(-5V+1)+5(8+7V)=33 | | 3s+4=25 | | 2(3x-7)=3x-5 | | X+(-4)=8 | | 2x*x^2-16*4x+3=0 | | 5(6+8B)+8(B-5)=-10 | | m-4m+12=3 | | 5x+10=9x+15 | | [(x-2)-5][(x-2)+3]=0 | | 18+2x=-54 | | 17x+64=13 | | -256=8(7X-6)-4X | | 24x+7*8= | | 5a-2+b-3b+2a= | | 5x-3x+40=50 | | x+109=1+89 | | 3x^2-8x-19=0 |